Digitalization of Ecotourism of The Limbungan Traditional House of Perigi Village: Implementation of SDG 8 for Sustainable Local Economic Growth - Salman Al Farizi; Pahrudin; Qurratul Aini (Fakultas Ekonomika dan Bisnis Universitas 17 Agustus 1945 Semarang, 2026)
The Limbungan Traditional House in Perigi Village, East Lombok, is one of the cultural heritage of the Sasak Tribe which has high ecological and cultural value, but its potential has not been optimally utilized as a competitive ecotourism destination. The purpose of this study is to analyze the digitalization-based branding model that can be applied to the ecotourism area, as well as examine its relationship with the achievement of Sustainable Development Goal point 8 (SDG 8), namely inclusive economic growth and the creation of decent jobs. The method used is qualitative descriptive with a case study approach, involving field observations, in-depth interviews with tourism awareness groups (pokdarwis), local MSME actors, and village stakeholders, as well as analysis of tourism policy documents. The results show that the implementation of digital branding through social media, online booking platforms, cultural video content, and collaborations with local content creators has been proven to significantly increase destination visibility. The designed branding model includes three main dimensions: digital cultural identity, ecotourism narrative, and an integrated MSME ecosystem. This transformation opens up economic opportunities for local tour guides, homestay managers, cultural craftsmen, and traders of typical products or MSMEs in the area. This research emphasizes that the integration of digital branding in the management of cultural ecotourism is not only a promotional strategy, but also an instrument of local economic development that is in line with the principles of sustainability of SDG 8. These findings imply that further research is needed to examine the long-term economic impact of digital branding on local communities, to conduct comparative studies across other village-based cultural ecotourism destinations, and to develop measurable indicators for evaluating the contribution of digital branding to SDG 8 achievement.